The role of the state audit in the public procurement process - Case of the Republic of North Macedonia - Dionisijev, Ivan (Faculty of Economics - Skopje, 2020)
Public procurement is of great importance in the development of the economy, especially in developing countries. In order to reduce corruption in the implementation of public procurement, this paper contributes to understanding the role of the Supreme Audit Institutions, in our country - the State Audit Office, in determining irregularities in the field of public procurement. The aim is to prove that if a larger number of audit engagements are carried out and a larger number of audit reports are issued, then a larger number of findings related to irregularities in the area of public procurement will be revealed. Also, the paper reviews the most important categories of identified sub-findings by state auditors for a period of 9 years, from 2011 to 2019. Processing of paper used data analysis, statistical calculations, and similar methods for data analyzing. Used methods are qualitatively and quantitatively supporting the thesis of this paper.
Keywords: public procurement, state audit, audit reports, findings